(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The susceptibility of West Java to landslides, coupled with its high population density, prompts research into landslide potential in the region. Notably, Gunung Batu and Graha Puspa in West Bandung Regency feature substantial andesite slopes situated along the Lembang fault and serve as tourist attractions. This study aims to assess the stability of these slopes using rock mass rating (RMR) and slope mass rating (SMR). The analysis integrates methods like rock mass classification (RMR), kinematics analysis, and empirical slope stability analysis (SMR), drawing on data obtained from uniaxial compressive strength (UCS) tests and scanline surveys. The andesite slopes exhibit RMR values ranging from 74 to 81, indicating good to very good rock mass quality. Design parameters and engineering properties are identified, including rock mass cohesion and internal friction angle, suggesting safe cut slope angles. Specific slopes are found susceptible to toppling or wedge failures. SMR values range from 72 to 96, categorizing the slopes as class I-II, indicating stability and a low probability of failure. Minor reinforcement options like scaling, toe ditch, fence, and spot bolting are proposed. Considering West Java’s seismic and rainfall risks, the study recommends further modelling to incorporate variations in seismic acceleration and water content. The method would yield safety factors and cut-off values under different slope conditions, enhancing the understanding and management of landslide risks in the region.